THE METHODS AND STRATEGIES OF PHYSICAL PREPARATION APPLIED TO FIGHTERS IN DIFFERENT COMBAT SPORTS: A NARRATIVE LITERATURE REVIEW (REMUNOM, 2026)
This research aimed to conduct a narrative literature review on the methods and strategies of physical preparation applied to fighters in different combat sports. A narrative literature review was carried out using the descriptors and their synonyms: "Combat Sports", "Physical Conditioning", "Periodization", "Sports Psychology", "Physical Education and Training". The search was conducted in the Google Scholar and PubMed databases. Studies that presented the descriptors and their synonyms in the title or abstract of the text were selected, in order to contribute to the findings on the topic of this research. 20 articles were included in this research. Based on the analyzed articles, four major thematic axes were structured: 1) (Bio)motor capacities in physical preparation for fighters; 2) The importance of the physical education professional in planning the physical preparation of fighters; 3) Psychological, technical and tactical preparation in the preparation of fighters; 4) Periodization model in the physical preparation of fighters. It is concluded that the physical preparation of fighters is multifaceted, as it must consider motor skills such as speed, power, strength, agility, flexibility, motor coordination, aerobic and anaerobic conditioning. In addition to these, technical, tactical, psychological, physiotherapeutic, and nutritional aspects are also considered. The role of the physical education professional is essential to ensure the proper evaluation, analysis, and organization of the fighter's physical preparation. In this process, interprofessional work is important to guarantee the fighter's athletic performance.